COVID-19 vaccine uptake and associated factors among adolescents and youths: Findings and implications for future vaccination programmes. - Steward Mudenda; Johanna C Meyer; Joseph O Fadare; Olayinka O Ogunleye; Zikria Saleem; Scott K Matafwali; Victor Daka; Billy Chabalenge; Jacob Chama; Moses Mukosha; Phumzile Skosana; Bwalya A Witika; et al. (Public Library of Science (PLoS), 2023)
Adolescents and youths are a key part of the population that needs to be protected against the coronavirus disease 2019 (COVID-19). This is because they are more likely to spread the virus to vulnerable individuals. In view of these concerns, this study investigated the uptake of COVID-19 vaccines and associated factors among adolescents and youths attending secondary schools in Zambia. This cross-sectional study was conducted among 1500 school-going adolescents in Lusaka from September 2022 to November 2022. Overall, 1409 participants took part giving a response rate of 94%. Only 29.2% (n = 411) of the participants were vaccinated against COVID-19 at the time of the study. Compared to their unvaccinated counterparts, vaccinated adolescents and youths scored higher for knowledge (66.2% vs 57.8%) and attitudes (76.7% vs 39.4%) regarding COVID-19 vaccines. Healthcare workers, family/friends and social media were key sources of information regarding the vaccine. Factors associated with increased vaccine uptake were positive attitudes (AOR = 33.62, 95% CI: 19.92-56.73), indicating it was stressful to follow COVID-19 preventive measures (AOR = 1.47, 95% CI: 1.09-1.99), participants in Grade 12 (AOR = 3.39, 95% CI: 1.94-5.91), Grade 11 (AOR = 2.59, 95% CI: 1.94-5.91), Grade 10 (AOR = 3.48, 95% CI: 1.98-6.11) and Grade 9 (AOR = 3.04, 95% CI: 1.74-5.32) compared to Grade 8. This study found a relatively low uptake of COVID-19 vaccines among adolescents and youths in Zambia. There is a need to provide adequate strategies to address knowledge and attitude gaps regarding COVID-19 vaccines to improve uptake and reduce future morbidity and mortality.